Microbial exposure to dairy farmers' dwellings and COPD occurrence. Issue 4 (4th July 2019) - Barrera, Coralie; Rocchi, Steffi; Degano, Bruno; Soumagne, Thibaud; Laurent, Lucie; Bellanger, Anne-Pauline; Laplante, Jean-Jacques; Millon, Laurence; Dalphin, Jean-Charles; Reboux, Gabriel
ABSTRACT: Dairy farming is a risk factor for chronic obstructive pulmonary disease (COPD). The aim was to determine predictive markers either in blood samples or in dwelling dust samples by comparing COPD and healthy controls with or without farming activity. Dust was collected and analyzed by real-time quantitative PCR. ELISA and DELFIA® were performed to assay the level of specific IgG and IgE of 10 targeted microorganisms. The dwelling exposure of farmers was higher than in the non-farmers (Especially Eurotium amstelodami and Lichtheimia corymbifera ). The IgG response against Wallemia sebi and Saccharopolyspora rectivirgula was more often higher in the farmers than the non-farmers. However, exposure and sensitization to the microorganisms tested cannot explain the occurrence of COPD in the dairy farmers' population. COPD development is probably caused by multiple factors associated with exposure over a period of several years.